Industry Interview Questions: Halal Promotional Language - Ariffin, Adlina (2021)
These were interview questions that were used to collect data for my research entitled "Developing a Model on Effective Promotion of Halal Concept to Increase Halal Awareness through Multi-Perspective Approaches for the Halal Food Industry".